2015
DOI: 10.1155/2015/215971
|View full text |Cite
|
Sign up to set email alerts
|

“Forget to Whom You Have Told This Proverb”: Directed Forgetting of Destination Memory in Alzheimer’s Disease

Abstract: Destination memory is the ability to remember the receiver of transmitted information. By means of a destination memory directed forgetting task, we investigated whether participants with Alzheimer's Disease (AD) were able to suppress irrelevant information in destination memory. Twenty-six AD participants and 30 healthy elderly subjects were asked to tell 10 different proverbs to 10 different celebrities (List 1). Afterwards, half of the participants were instructed to forget the destinations (i.e., the celeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 59 publications
0
6
0
1
Order By: Relevance
“…This account has been supported by studies showing that older adults are prone to interference in verbal working memory, visuospatial working memory, and even implicit memory [52, 53]. Regarding AD, studies have shown difficulties in suppressing no longer relevant information in working memory [33], semantic memory [34], and episodic memory [35, 36]. Therefore, AD patients tend to maintain information from past task performance, even when this information is no longer relevant for the current situation [31].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This account has been supported by studies showing that older adults are prone to interference in verbal working memory, visuospatial working memory, and even implicit memory [52, 53]. Regarding AD, studies have shown difficulties in suppressing no longer relevant information in working memory [33], semantic memory [34], and episodic memory [35, 36]. Therefore, AD patients tend to maintain information from past task performance, even when this information is no longer relevant for the current situation [31].…”
Section: Discussionmentioning
confidence: 93%
“…These deficits have been observed in studies using the directed forgetting task in which participants are typically instructed to remember or forget certain types of information for a later memory test [32]. Research using the directed forgetting method suggests that AD patients experience difficulties when they are asked to suppress no longer relevant information in working memory [33], semantic memory [34], and episodic memory [35, 36].…”
mentioning
confidence: 99%
“…The involvement of inhibition in decline of autobiographical in aging has been pointed out by a study showing a diminished ability to inhibit no-longer relevant semantic autobiographical memories in normal aging [43]. According to these authors, difficulties in inhibiting irrelevant information hamper memory retrieval by activating irrelevant memories at the expense of relevant ones (for a similar view, see [44][45][46]. Interestingly, another study has found that updating, rather than inhibition, is the source of diminished autobiographical specificity in normal aging, supporting the core role of updating in autobiographical functioning in aging [47].…”
Section: Discussionmentioning
confidence: 99%
“…Emotional and personality characteristics variables may also be considered; for instance, older adults may simply tend to "speak their minds" more than younger adults. As for pathological aging, it would be of interest to investigate whether inhibitory compromise, as observed in Alzheimer disease [36][37][38][39][40] , would be associated with a low tendency to deceive.…”
Section: Discussionmentioning
confidence: 99%